2014
DOI: 10.1186/2251-6581-13-52
|View full text |Cite
|
Sign up to set email alerts
|

Association between dietary intake and seasonal variations in postmenopausal women

Abstract: BackgroundEvidence supports that increasing number of postmenopausal women are suffering from one or more chronic diseases. Dietary patterns have a pivotal role in maintaining human health. The aim of this study was to characterize the nutrients and energy intake in postmenopausal women, with the special focus on seasonal variation effect in their food intake.MethodsThe study population consisted of 30 postmenopausal women referred to Dr. Shariati Hospital, Tehran (Iran). Socio-demographic characteristics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 25 publications
2
14
3
Order By: Relevance
“…2, 3, 57, 9, 10, 19, 20, 24 In contrast to our results, some studies found differences in energy, carbohydrate, and protein intake across seasons. 2–4, 6, 8, 11, 20 In a study by Ma et al, 20 which is perhaps the study with the most similar population to the current study, differences in daily caloric intake by season were reported.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…2, 3, 57, 9, 10, 19, 20, 24 In contrast to our results, some studies found differences in energy, carbohydrate, and protein intake across seasons. 2–4, 6, 8, 11, 20 In a study by Ma et al, 20 which is perhaps the study with the most similar population to the current study, differences in daily caloric intake by season were reported.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous research is not consistent in its comparison of seasons. Although most studies have looked at differences across all four seasons, 2, 3, 68, 1013, 17, 18, 20, 21, 24 a few have only analyzed differences between summer and winter. 4, 5, 9, 19 The nutrients analyzed, the division and definition of food groups and seasons, and adjustment for confounding factors are also inconsistent across studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The researchers found a significantly higher intake of vitamin K in the spring, summer, and autumn compared to the winter. Unfortunately, these authors did not further specify vitamin K and did not provide any information about consumption of different food items containing vitamin K [50]. A study in older individuals to calculate the desired duration of a diet recording to estimate the individual vitamin K intake concluded that 13 24-hour recalls are ideal to record intraindividual variance.…”
Section: Dietary Intake Of Menaquinonesmentioning
confidence: 99%